Effect of A Physical Exercise Routine on Serum Glucose and Lipids Levels in Tertiary Level Hospital Workers: Preliminary Results (Revista de Medicina Clinica, 2025)
Introduction: Regular exercise increases insulin sensitivity, improves cardiorespiratory fitness, and optimizes blood sugar control. The objective was to evaluate whether there are differences in glucose and lipid levels after a physical exercise routine in workers during working hours of a public hospital. Patients and methods: A prospective, analytical, longitudinal intervention study was designed. Participants exercised 30 minutes daily for 12 weeks. Blood samples were taken at the beginning and at the end of glucose, HbA1c, total cholesterol, LDL, HDL, and triglycerides. SPSS version 24 for Windows was used, descriptive statistics and central tendency, relative and absolute frequencies, Wilcoxon rank tests were used to evaluate differences considering a p value < 0.05). Graphs and tables were used for their interpretation. Results: Of the 19 workers included in the study, 15 completed the follow-up, female in (73%) mean age of 44.13 years. Initial laboratory results showed levels of glucose, HbA1c, total cholesterol, LDL, HDL and triglycerides, which improved significantly after the exercise routine. Statistical tests (Wilcoxon) revealed differences in glucose, HbA1c, LDL, HDL and triglycerides (p0.05), except for total cholesterol (p=0.11140). Conclusion: The results show that 30 minutes of exercise improves blood sugar levels, glycated hemoglobin (HbA1c), low-density lipoproteins (LDL), high-density lipoproteins (HDL) and triglycerides. Although cholesterol levels did not change.
Keywords: Physical exercise; Occupational health program; Glycemia; Lipids, Glycated hemoglobin